Between Hegemonic and Subordinated Masculinities: Men, Their Sexuality and Politics of Masculinity in Contemporary Lithuania - Tereškinas, Artūras (Sociologija. Mintis ir veiksmas, 2004)
The article examines hegemonic and subordinated forms of masculinity in contemporary Lithuania. Using the opinion survey „The Crisis of Male Roles in Lithuania” (2002) and a wide array of literature theorizing men and masculinities, it attempts to answer the following questions: how can we assess the influence of different masculinities to men themselves and gender policies in Lithuania? What kind of masculinity policy can support a feminist project of social transformation?The survey „The Crisis of Male Roles in Lithuania” allows us to conclude that both Lithuanian men and women largely support traditional norms of hegemonic masculinity. This masculinity is based on heterosexuality, economic autonomy, being able to provide for one’s family, being rational, being successful, keeping one’s emotions in check and not doing anything considered feminine.The dominant form of masculinity in Lithuania is constructed not only in relation to femininities but also in relation to subordinated and marginalized masculinities, particularly homosexual masculinities. Homosexuality is the repository of everything that is symbolically expelled from hegemonic masculinity. As the survey demonstrates, homophobia is much stronger among men than women in Lithuania. This can be explained by the fact that in order to be „real men” males have to separate themselves from both women and homosexual men. Furthermore, Lithuanian men’s negative attitude towards homosexuality can also be related to their traditional attitudes toward gender roles and family. The view that gays transgress the gender system is rather widespread among them.The author argues that the dominance of a single model of masculinity at the expense of multiple masculinities makes men more vulnerable to acts of violence against themselves and their families. The article advocates self-awareness and critical reflection about gender identities among men and male groups that could help dismantle hegemonic masculinity and dispel the notion that there is only one way to be a ‘real man’. Promoting models of masculinity along less sexist, homophobic and misogynist lines could benefit both women and men.
Keywords: masculinity; hegemonic masculinity; subordinated masculinity; homosexuality